2010
DOI: 10.3324/haematol.2010.037390
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous injections of low-dose veltuzumab (humanized anti-CD20 antibody) are safe and active in patients with indolent non-Hodgkin's lymphoma

Abstract: The online version of this article has a Supplementary Appendix. BackgroundSubcutaneous injections of anti-CD20 antibodies may offer benefits to both patients and the healthcare system for treatment of B-cell malignancies. Design and MethodsA pilot study was undertaken to evaluate the potential for subcutaneous dosing with 2 nd generation anti-CD20 antibody veltuzumab in patients with CD20+ indolent non-Hodgkin's lymphoma. Patients with previously untreated or relapsed disease received 4 doses of 80, 160, or 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Two other studies with SC veltuzumab also administered 80, 160 or 320 mg SC doses, again finding activity in all dose groups with increased serum levels and no obvious exposure-response relationship, but these were studies in Bcell malignancies and with too few patients to evaluate whether response duration improved with higher doses. 3,4 One tentative explanation for the apparent lack of dosedependence of responses might be that even 80-mg doses of SC veltuzumab result in B-cell depletion in peripheral blood irrespective of response. In this model, response would depend on whether B-cell clearance leads to platelet response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other studies with SC veltuzumab also administered 80, 160 or 320 mg SC doses, again finding activity in all dose groups with increased serum levels and no obvious exposure-response relationship, but these were studies in Bcell malignancies and with too few patients to evaluate whether response duration improved with higher doses. 3,4 One tentative explanation for the apparent lack of dosedependence of responses might be that even 80-mg doses of SC veltuzumab result in B-cell depletion in peripheral blood irrespective of response. In this model, response would depend on whether B-cell clearance leads to platelet response.…”
Section: Discussionmentioning
confidence: 99%
“…1 Clinical studies in B-cell malignancies found that relatively low doses of this antibody were effective when administered by intravenous infusion 2 or subcutaneous (SC) injection. 3,4 Case reports in systemic lupus erythematosus 5 and pemphigus vulgaris 6 indicated that veltuzumab might also be effective in autoimmune disease. We therefore undertook a clinical study in immune thrombocytopenia (ITP), previously reporting that low doses of intravenous or SC veltuzumab could improve platelet counts when administered twice 2 weeks apart, 7 W e compared two dosing schedules for subcutaneous injections of a low-dose humanized anti-CD20 antibody, veltuzumab, in immune thrombocytopenia.…”
Section: Introductionmentioning
confidence: 99%
“…We found it reasonable that the AME-133E s.c. monkey studies may correlate with s.c. ocaratuzumab. Additionally, we noted that veltuzumab, another s.c. anti-CD20 mAb, 16 is in development for B cell malignancies; however, a preclinical comparison of each antibody to rituximab suggests that ocaratuzumab has a nearly 80-fold increase in binding affinity compared with veltuzumab. 8 Obinutuzumab, a glyco-engineered type II anti-CD20 mAb, is also the most recently approved by the US Food and Drug Administration for use in combination with chlorambucil for front-line therapy of CLL patients who are unfit for more aggressive regimens secondary to age or medical comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…They found that this approach constituted an effective therapy that was able to activate effector mechanisms without causing substantial loss of CD20. Moreover, Goldenberg et al reported that lower doses of the CD20 mAb veltuzumab, given either intravenously or subcutaneously, also have demonstrable activity in the treatment of lymphoma (Morschhauser et al, 2009;Negrea et al, 2011). There is also additional, historic precedence for a low-dose strategy.…”
Section: Concluding Remarks: the Way Forwardmentioning
confidence: 99%